Employees' perspective of ethics / Rabiatul Alawiyah Zainal Abidin, Raziah Mohamed Sadique, Norhayati Alias and Noraizah Abu Bakar - Zainal Abidin, Rabiatul Alawiyah; Mohamed Sadique, Raziah; Alias, Norhayati; Abu Bakar, Noraizah (2012)
The increasing number of companies' collapses, due to corporate fraud or misconduct, has triggered the need to understand why this happened. One of the major contributors to these activities is poor ethical values among company's employees. Therefore, it is important for companies to have a proper and effective code of conduct and ethics program in order to prevent corporate fraud. The aim of this study is to determine the perception and understanding of employees towards companies' code of conduct and ethics program. Questionnaires were distributed to a sample of companies in the Klang Valley which asked on the perception of employees towards companies' code of conduct and ethics program. The results indicates that majority of companies surveyed are having this program available at their companies. It is also found out that majority of the employees understand about these two programs; understand the importance of having these two program for the companies and the managers pay serious attention to the ethics program. Nevertheless, a small percentage of respondents did not understand and still not clear with the code and ethics programs. As a conclusion, this study found out that companies do have sufficient ethics standards and ethics program. However, there is room of improvement particularly in making sure that employees fully understand the ethics standards and ethics program. This implies that companies need to have training and seminars to ensure their employees understand these. Therefore, future study should look into the ethics standards and ethics program itself to ensure it has been carried out effectively.